A Positive Psychology Perspective on Positive Emotion and Foreign Language Enjoyment Among Chinese as a Second Language Learners Attending Virtual Online Classes in the Emergency Remote Teaching Context Amid the COVID-19 Pandemic - Wang, Qing; Jiang, Yuhong (Frontiers in Psychology, 2022)
This study adopted a positive psychology perspective to investigate positive emotion and foreign language enjoyment among Chinese as a second language (CSL) learners in an emergency remote teaching (ERT) context amid the COVID-19 pandemic. A set of 90 preparatory Chinese language students (40 males and 50 females) was assessed for their level of foreign language enjoyment using the Foreign Language Enjoyment Scale (FLES). Participles’ scores on self-perceived language achievement and actual test scores were adopted as the measurement of their Chinese language proficiency. The results revealed that: (1) CSL learners experienced high level of FL enjoyment in an online learning context, (2) no significant correlation was found between FLE and leaners’ actual language achievement nor between FLE and their self-perceived achievement, (3) female learners showed higher FLE than male learners and gender was found to have a significant effect on FLE-Private, (4) participants’ geological location, i.e. whether in China or at home countries, significantly influenced their FLE, (5) participants’ regional group was not a significant predictor of FLE, and (6) teacher-related variables and learner self-perceptions of achievement were strong predictors of FLE among CSL learners. The findings highlight the importance of teacher’s role in an online learning environment and suggest that FLE may not boost performance in the short term for language beginners but is still conducive in the long run. Implications for both teachers and learners, and suggestions for future researches are provided.